KOLABORASI MULTI LEVEL DALAM PENANGGULANGAN KEMISKINAN EKSTREM DI 7 PROVINSI DAN 35 KABUPATEN PRIORITAS DI INDONESIA (STUDI KASUS DI PROVINSI JAWA TENGAH) - Hidayat, Mohamad Taufiq; Kurniasih, Denok; Tobirin, Tobirin (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The purpose of this research is to describe "collaborative" in poverty alleviation in 7 Provinces and 35 Priority Districts in Indonesia by sampling Central Java province, the parties involved and what poverty reduction strategies are used in Central Java. The method used was descriptive qualitative and the theoretical approach of "Ansell and Gash (2007)" became the basis of this research. The results of the study show that multi-level collaboration in extreme poverty reduction, especially in the Central Java region, has succeeded in reducing the extreme poverty rate both at the provincial and district levels. Leadership is a key factor in the success of this collaboration. This is because it is able to facilitate and cooperate with all components to collaborate. In addition, it provides strong trust, so as to build commitment in all parties to be responsible for their respective duties.